New regulators of the tetracycline‐inducible gene expression system identified by chemical and genetic screens. Issue 10 (11th September 2022) - Colicchia, Valeria; Häggblad, Maria; Sirozh, Oleksandra; Porebski, Bartlomiej; Balan, Mirela; Li, Xuexin; Lidemalm, Louise; Carreras‐Puigvert, Jordi; Hühn, Daniela; Fernandez‐Capetillo, Oscar
Abstract : The tetracycline repressor (tetR)‐regulated system is a widely used tool to specifically control gene expression in mammalian cells. Based on this system, we generated a human osteosarcoma cell line, which allows for the inducible expression of an EGFP fusion of the TAR DNA‐binding protein 43 (TDP‐43), which has been linked to neurodegenerative diseases. Consistent with previous findings, TDP‐43 overexpression led to the accumulation of aggregates and limited the viability of U2OS. Using this inducible system, we conducted a chemical screen with a library that included FDA‐approved drugs. While the primary screen identified several compounds that prevented TDP‐43 toxicity, further experiments revealed that these chemicals abrogated the doxycycline‐dependent TDP‐43 expression. This antagonistic effect was observed with both doxycycline and tetracycline, and in several Tet‐On cell lines expressing different genes, confirming the general effect of these compounds as inhibitors of the tetR system. Using the same cell line, a genome‐wide CRISPR/Cas9 screen identified epigenetic regulators such as the G9a methyltransferase and TRIM28 as potential modifiers of TDP‐43 toxicity. Yet again, further experiments revealed that G9a inhibition or TRIM28 loss prevented doxycycline‐dependent expression of TDP‐43. In summary, we have identified new chemical and genetic regulators of the tetR system, thereby raising awareness of the limitations of this approach to conduct chemical or genetic screening in mammalian cells. Abstract : Promoters harbouring tetO sequences enable the regulated expression of a gene of interest in response to tetracycline and related chemicals. By conducting chemical and genetic screens, Colicchia et al . identify novel drugs and mutations that impair tet‐dependent gene expression. These findings raise awareness of the potential limitations of using Tet‐regulated gene expression systems for conducting phenotypic screens.